THE IMPACT OF PLANTAIN (Musa paradisiaca L.) PEEL LIQUID ORGANIC FERTILIZER ON THE GROWTH OF PAKCOY (Brassica rapa L.) - Norhajah, Siti; Irhasyuarna, Yudha; Putri, Rizky Febriyani (Transpublika Publisher, 2023)
Plantain peels are an underutilized waste product that is often discarded without being processed, resulting in an unpleasant odor in the surrounding environment. However, plantain peels are rich in nutrients that can benefit plant growth, making them a potential ingredient in liquid organic fertilizers. This study aimed to investigate the growth response of pakcoy plants when treated with POC (plantain peel organic fertilizer). A complete randomized design (CRD) was used with five treatments and four replications in each treatment, including a control group (N0) and four POC treatments (N1-N4) with varying concentrations (50-125 ml). The results showed that plantain peel POC had a significant effect on plant height growth, number of leaves, and fresh weight in the N4 treatment, which had the highest concentration of 125 ml plantain peel POC.